The Tongde Picritic Dikes in the Western Yangtze Block: Evidence for Ca. 800-Ma Mantle Plume Magmatism in South China during the Breakup of Rodinia - Li, X.; Zhu, W.; Zhong, H.; Wang, Xuan-Ce; He, D.; Bai, Z.; Liu, F. (University of Chicago, 2010)
Secondary ion mass spectroscopy U-Pb zircon ages and mineralogical, geochemical, and Nd isotopic data are reported for the Tongde picritic dikes in the Yanbian area of the western Yangtze Block, South China. The picritic dikes, which intruded in the ca. 820-Ma Tongde complex, are dated at 796+-5 Ma. Most of the picritic rocks are highly porphyritic (ca. 15–35 vol% phenocrysts) with dominant olivine (Fo = 82–92) phenocrysts that are high in CaO (up to 0.43 wt%), Cr2O3, and Ni. All the studied rocks are high-Ti and alkaline in composition and exhibit light rare earth element– enriched and “humped” incompatible trace-element patterns, similar to the alkaline basalts within the ocean islands and continental rifts. Variably high εNd(T) values between +6.9 and +8.7 indicate that these rocks were derived from an asthenospheric mantle source with inappreciable crustal contamination. Geochemical modeling suggests a primary melt of 22.7% MgO for batch melting and 21.4% MgO for fractional melting. The high MgO content in the modelled primary magmas implies a minimum melt temperature of >1400˚C and a mantle potential temperature of 1600˚– 1620˚C. The Tongde picritic dikes were therefore generated by melting of an anomalously hot mantle source with a potential temperature ca. 200˚C higher than that of the ambient mid-ocean ridge basalt–source mantle, similar to that of modern mantle plumes. Thus, the Tongde picritic dikes provide solid petrological evidence for the proposed Neoproterozoic mantle plume that led to the breakup of the supercontinent Rodinia.